The Implementation of Dwangsom in the Execution of Hadhanah Matters and its Relationship to the Ultra Petita Basis - Firdawaty, Linda; Mahmudah, Siti; Isa, Rozana (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
This article aims to examine the reasons why dwangsom is urgent in hadhanah cases and how it is implemented in hadhanah execution cases and its relationship with the ultra petita principle.  This article is empirical normative legal research with qualitative descriptive analysis method. The urgency of dwangsom in hadhanah cases is an effort to provide psychological pressure so that the defendant wants to carry out the judge's order voluntarily, namely handing over the child who is the object of the case. If the defendant does not hand over the child as the judge's decision, then the defendant must pay dwangsom. The institution of dwangsom is not widely known to the public, but dwangsom is an appropriate and effective solution because the surrender of children cannot be done through forced execution.  Dwangsom can be implemented in hadhanah cases if the plaintiff submits a dwangsom application. The petition must also explain the chronology of the plaintiff's reasons for requesting dowry. If dowry is not submitted in the petita, then the judge is not authorized to decide dowry, because granting dowry without a request from the plaintiff is an ultra petita action.